Supporting a graphic design dyslexic student: Utilizing multimedia tools and design applications - Ahmad, Manal; Nabhan, Rabih; Semaan, Simona; Khoueiry, Joe (Edelweiss Applied Science and Technology, 2025)
Dyslexia is a learning condition that affects both children and adults, limiting their ability to read, write, and spell. This case study focuses on Simon, a high-achieving student at a Lebanese private university who struggles in English language classes due to dyslexia. The purpose of this study is to examine how targeted interventions can improve his spelling skills and overall learning experience. The design combines a case study framework with mixed methods. The methodology integrates both qualitative and quantitative approaches, while the approach is inquiry-based and learner-centered. The study emphasizes the importance of phonological awareness in addressing these issues, exploring how a lack of it hinders the acquisition of basic skills. The current research examines the psychological and social effects of dyslexia on individuals, highlighting the importance of supportive learning environments. It utilizes multimedia-based learning procedures customized to Simon's design interests. Specifically, the study used high-frequency word repetition and video-based exercises to improve his spelling skills and foster autonomous learning. The findings demonstrate measurable improvement, showing that Simon's ability to accurately spell high-frequency words improved significantly, implying that multimedia tools can help dyslexic adults learn. In conclusion, practical implications suggest that adopting such a model incorporating multimedia tools can be of high value for dyslexic learners.